Values and values types differences among accounting and non-accounting students: A study on ITM students / Sharifah Norhafiza Syed Ibrahim - Syed Ibrahim, Sharifah Norhafiza (Universiti Teknologi MARA Cawangan Pahang, 2002)
The main objective of this study is to identify the differences between values and value types between accounting and non-accounting students of ITM. The research instrument used was Schwartz (1992) Values Questionnaires. It contains 56 values and was administered to final year accounting and business students in ITM. By grouping responses to the 56 values, ten value types were derived. Results of the research show that there are very few differences in values between accounting and business majors. The differences exist for three values, i.e. Mature Love, National Security and Successful. Further, none of the value types were significantly differed. More significant differences exist between responses of males and females (ten values - Sense of Belonging, Daring, Social Power, A World at Peace, Creativity, Curious, Obedient, Respect for Tradition, Social Justice and Pleasure and two value types Self- direction and Power). Very few differences were also found between responses of students from different environmental backgrounds, age groups (Influential), academic performances (Health) and parental income levels (Broadminded and Social Justice). The interaction between the independent variables such as between major and gender were also examined. As a result, this study finds that there were more similarities than differences in values and value types within those environments. An understanding of students' values and value types is favorable to educators, administrators and businesses. It is hoped that these findings are useful in recruiting, retention, scheduling, teaching and training of students and business professionals.